IMPLEMENTASI PROGRAM GASING (GEREJA BERSIH STUNTING) DI JEMAAT OVERA FATULULAT, AMFOANG TENGAH - Lette, Arman Rivat; Jumetan, Mili A. (STIKes Mitra Husada Medan, 2024)
Stunting is a form of growth failure due to the accumulation of nutritional deficiencies that last for a long time from pregnancy to 24 months of age. The aim of this research is to describe or describe the implementation of the GASING (Clean Stunting Church) program. The research method is qualitative research with an exploratory design and descriptive approach. The main informants are religious figures, while the supporting informants are health workers and mothers who receive GASING assistance. The number of informants selected was 7 people. Data collection was carried out by means of Focus Group Discussion (FGD), non-participant observation and in-depth interviews. The research was conducted in June-July 2024. The results showed that at the beginning of program planning due to the high number of stunting cases; Often attend meetings but there is no real follow-up; Input related to the benefits of eggs and the issue of sustainable balanced nutrition; and Feeling the church needs to take a role. The implementation of the program shows: it is implemented by distributing 7-10 eggs per week at the church on a regular basis; The target is pregnant women, breastfeeding mothers, and children under 2 years old; It has been running for 56 weeks and started with a chicken keeping group. The Monev Process shows that monitoring is carried out every week and every month; There is a KEK mother but the child is born 3.4 kg; The child's body length and weight increase; it is hoped that there will be cooperation with the village government and Health; and can be an example for other churches. The suggestion is that this program could be a good example or model in efforts to prevent and handle stunting in society.